The Impact of Agricultural Sector Development in 10 Provinces - Setiawan, Alvin; Barokatumminalloh, Barokatumminalloh; Fauzi, Pahrul (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2024)
Despite the large value of GRDP and investment at province level, the level of employment and income distribution still tends to fluctuate. The study aims to analyze the effect of development and investment in the agricultural sector on employment in the agricultural sector and income distribution. The type of this research is descriptive-quantitative using secondary data. This study uses multiple linear regression analysis of panel data. The analysis is divided into two models, the first model analyzes the impact of development and investment in the agricultural sector on employment in the agricultural sector, while the second model analyzes the same variables on income inequality. The results of the first model show that the development of the agricultural sector has a significant and positive effect on employment in the agricultural sector, while investment in the agricultural sector has an insignificant on employment in the agricultural sector. The results of the second model show that the development of the agricultural sector has a significant and negative effect on income inequality, while investment in the agricultural sector has an insignificant effect on income inequality. The implication of the results is that the government should maintain and improve the quality of the agricultural sector by implementing policies that encourage agricultural productivity and carry out equitable development of facilities and infrastructure to support agricultural activities in remote areas.